Improving Early Childhood Literacy Skills Through Storytelling and Picture Books Based on Local Wisdom for Early Childhood Educators - Kamariah, Kamariah; Harpriyanti, Haswinda; Saufi, Muhammad (Universitas Lambung Mangkurat, 2025)
This service activity will be carried out from August to September 2024 to improve early childhood literacy skills through fairy tale methods and picture reading books based on local wisdom. The main target of the activity is 22 PAUD, who are members of the PKG of Aluh-Aluh District, who will be given training regarding the use of more creative and interactive learning methods, including storytelling and picture reading books. Apart from that, storytelling assistance and the creation of reading corner trees were also provided at three sample schools, namely at Pembina Aluh-Aluh State Kindergarten, Al-Fatah PAUD, and Permain PAUD. This was done to overcome the problem of low literacy skills of early childhood in the area. Implementing this community service was carried out as on-on-in training, which consisted of three main stages: On-service training, on-job training, and in-service training. The findings from this activity indicate that educators became more creative and skilled in delivering literacy materials, which positively impacted children's reading interest and active participation in literacy activities at school. Additionally, implementing reading corners in schools successfully created an environment supporting children's literacy engagement. However, challenges such as limited resources and adapting methods for children with special needs still need to be addressed. This community service has positively improved early childhood literacy and recommends government support and ongoing evaluation to strengthen the program's long-term impact.